MIMO Antenna Design for 5G Applications - Kaur, Navneet (My University, 2023)
The emergence of fifth-generation wireless communication has brought significant advancements in technology, data rates, size, and overall system performance. To fully leverage the capabilities of 5G networks, accommodating multiple communication technologies within limited space has become an increasingly significant challenge. Today's modern gadgets and devices are compact yet versatile, serving as multimedia systems that support a wide range of applications, including virtual reality, high-end online gaming, and multi-person video calling. With the growing complexity of these advanced applications, higher data rates are needed, necessitating greater bandwidth from the communication technology being employed. In order to fully exploit the capabilities of 5G networks, efficient and robust antenna systems are essential. This thesis focuses on the design and optimization of antennas specifically tailored for sub-6GHz 5G applications, aiming to enhance coverage and capacity in 5G wireless networks. The initial phase of this research involves a comprehensive review of the unique requirements and challenges associated with sub-6GHz 5G frequency bands. Factors such as spectrum allocation, performance parameter and diversity parameter of MIMO antenna are analyzed to gain a deeper understanding of the design considerations for antennas operating in this frequency range. Based on the insights gained from the analysis a novel antenna design methodology is proposed in thesis. The methodology incorporates, optimization algorithms, design, analysis and testing of proposed antennas. Key antenna parameters, including impedance matching, bandwidth, gain, radiation patterns and isolation between antenna elements are carefully considered to ensure optimal performance in terms of coverage, capacity, and quality of service. In the present work, we started with a single element antenna design and then extended it for dual/multiple element antenna designs for 5G applications. In the first antenna design, we designed and optimized a single element microstrip patch antenna for 3.4-3.8 GHz band of 5G.The optimization of geometrical parameters has been done using evolutionary optimization techniques. In particular, we optimized the geometrical parameters using Particle Swarm Optimization, Bat algorithm, Differential Evolution, and Artificial Bee Colony algorithm. The final optimized antenna resonates at 3.6 GHz with a measured -10dB bandwidth of 400 MHz, 4.78 dBi gain and radiation efficiency of 74%.Thesepromising results allow the proposed antenna is suitable to be employed in 5G wireless applications such as wireless routers, tablet devices etc. In the second antenna design, we further extended our work on designing a compact dual-element MIMO antenna with dual-band characteristics for GSM-900 (0.88-1.08 GHz) and sub-6 GHz 5G band (3.11-4.63 GHz).However, when both elements of the antenna are placed on a single substrate, poor isolation of the MIMO antenna occurs, necessitating decoupling structures for improved isolation, which increases the antenna's complexity. As a solution, we have developed a MIMO antenna with a self-isolation of 19dB, reducing the need for extra decoupling circuits. The most important feature of this proposed antenna is that it is able to achieve high isolation (19 dB) and broad bandwidth (1.52 GHz) for 5G applications simultaneously without employing external decoupling structures. For third antenna design, we have designed quad-element antenna for practical application of 5G. Portable devices like smart-phones and tablets, as well as on body and automotive applications of 5G, require multiple antenna elements to enable high-speed data transfer and reduce signal interference. These antennas work together to provide a stronger and more stable connection, improving the overall performance of the device. The designed antenna exhibits a high peak gain of 6dB along with satisfactory diversity results. The proposed MIMO antenna also exhibits good performance in different practical scenarios such as on-body(phantom), integration of antenna in housing and on-vehicle roof for automotive application. In summary, three antenna designs are demonstrated single-band, dual and wide band operations within sub-6 GHz applications of 5G. The objectives of the research work to achieve compact size, enhanced gain and high isolation of multiple input multiple output antenna has been successfully accomplished. All the designed antennas underwent simulation using CST microwave studio suite to assess their performance. Subsequently, antenna structures were fabricated and experimentally tested for the validation of results. The s-parameters of designs were measured using a Vector Network Analyzer (VNA) available in the Microwave and Antenna Research Laboratory of Thapar Institute of Engineering and Technology (TIET), Patiala. The radiation patterns of all designs were measured in anechoic chamber, which is available in Indian Institute of Technology (IIT), Roorkee.
PhD Thesis_12-10-2023
Keywords: MIMO antenna; 5G; Self-Isolation; Diversity; Optimization techniques